2008
DOI: 10.1186/1532-429x-10-41
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiovascular magnetic resonance of late gadolinium enhancement and diastolic wall thickness to predict recovery of left ventricular function after coronary artery bypass surgery

Abstract: Background: The objective was to compare the value of late gadolinium enhancement (LGE) and end-diastolic wall thickness (EDWT) assessed by cardiovascular magnetic resonance (CMR) in predicting recovery of left ventricular function after coronary artery bypass surgery (CABG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…S car as a result of acute myocardial infarction (AMI) and chronic myocardial infarction (CMI) has important prognostic implications (1)(2)(3)(4). There is growing evidence suggesting that cardiac magnetic resonance (CMR) using the late gadolinium enhancement (LGE) technique can be considered the gold-standard modality for its assessment (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…S car as a result of acute myocardial infarction (AMI) and chronic myocardial infarction (CMI) has important prognostic implications (1)(2)(3)(4). There is growing evidence suggesting that cardiac magnetic resonance (CMR) using the late gadolinium enhancement (LGE) technique can be considered the gold-standard modality for its assessment (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Patients with 5 or less segments with a DE/wall thickness ratio C50% can be expected to show reverse LV remodeling with a sensitivity of 86% and specificity of 75%, and in patients with 2 or fewer segments with a DE/wall thickness ratio C75%, the sensitivity and specificity are 71 and 67%, respectively. Most papers published to date, focus on the ability of DE-MRI to predict myocardial viability defined as an improvement of segmental motion within a couple of months (usually 3-6) after CABG [8][9][10][11][12][16][17][18][19][20][21]. The improvement of segmental function in these studies was inversely proportional to the extent of DE on MRI; the higher the DE/wall thickness ratio, the lower the chance that a segment could improve its function after revascularization.…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, both single-photon-emission computed tomography (SPECT) and magnetic resonance imaging (MRI) have been shown to be powerful predictors of myocardial viability after surgery [8][9][10][11][12][13][14]. The underlying mechanism of reversible LV dysfunction in viable myocardium can be either myocardial stunning (contractile dysfunction after an ischemic insult despite adequate perfusion) or hibernation (contractile dysfunction and decreased myocardial metabolism as a result of prolonged reduction of perfusion) [15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…CMR studies have also found that a decrease in end diastolic wall thickness prevents functional improvement after a coronary artery bypass surgery [12]. Hyperenhancement, end diastolic wall thickness, and resting wall motion grade have been integrated through logistic regression to create a model to predict functional improvement after revascularization [13]. Although this regression demonstrated that hyperenhancement was the most important predictor of functional improvement, the addition of end diastolic wall thickness and wall motion grade increased the model's accuracy [13].…”
Section: Introductionmentioning
confidence: 97%